Phenotypic stability of pea (Pisum sativum L.) in the production area of Nariño, Colombia - Cadena-Guerrero, Máryory Maricela (2021)
Introduction. The pea (Pisum sativum L.) is a legume crop of great importance for the peasant economy in the high Andean zone of the department of Nariño, Colombia. Most of the pea production in this department is marketed as fresh pods; however, it is necessary to strengthen the local dry bean market, which requires varieties adapted to regional conditions. Objective. To evaluate fifteen pea genotypes for phenotypic stability of dry grain yield, in the Nariño production zone. Materials and methods. Between 2013 and 2014, fifteen pea genotypes were evaluated in three Nariño environments. The experiments were established with a randomized complete block design and four replicates. The GGE biplot model was used for dry grain yield stability analysis. Results. In the analysis of variance across the three environments, there were significant effects (p<0.05) of environments (A), genotypes (G), and GA interaction, for dry grain yield and number of grains per pod. The average yield for all environments was between 747.5 and 1357.3 kg ha-1 and the grains per pod between 4.4 and 5.4. The genotypes ARUDN-3562 and VOUDN-7350 stood out for being stable and for their high yields (kg ha-1) with 1357.3 and 1144.1, respectively, which exceeded the general average (1057.9) and were statistically similar to the controls Alcala (1227.8), Obonuco Andina (1238.1), and Santa Isabel (1013.6). Conclusion. The genotypes studied showed high variability in yield and phenotypic stability, which will allow expanding the working collection for pea improvement in Nariño. The genotypes ARUDN-3562 and VOUDN-7350 stood out and could be used individually or as parental.